Creative Problem Solving Accompanied by Wordwall as an Assessment Media: Does it Have an Impact on Students' Higher Level Physics Thinking Abilities? - Andini, Alfenda Dwi; Mahardika, I Ketut; Maryani (International Journal of Education and Teaching Zone, 2024)
This study aims to examine the effect of the Creative problem-solving learning model accompanied by wordwall assessment media on the higher-order thinking Skills (HOTS) ability of physics class XI students of SMAN Balung. This research used an experimental method with a group pretest-posttest design. The data collection technique used was a written test. The tests given were objective pretest and posttest tests. The data obtained was tested using the Kolmogorov Smirnov statistical test data normality test so that the sig value was obtained.  2 tailed > 0.05 then the mann whitney-u test was carried out and obtained a sig value. (2-tailed) of 0.041. So the results of data analysis of students' physics HOTS ability are 0.001 < 0.05. Based on the criteria used in decision-making in the Mann Whitney - u nonparametric statistical test, it can be concluded that HO is rejected and Ha is accepted, meaning that the average value of the experimental class is greater than the control class. so it can be concluded that the Creative problem-solving learning model assisted by wordwall assessment media has a significant effect on students' physics HOTS Skills ability.